Preparing Medical Specialists to Practice Genomic Medicine: Education an Essential Part of a Broader Strategy - Crellin, Erin; McClaren, Belinda; Nisselle, Amy; Best, Stephanie; Gaff, Clara; Metcalfe, Sylvia (Frontiers in Genetics, 2019)
Developing a competent workforce will be crucial to realizing the promise of genomic medicine. The preparedness of medical specialists without specific genetics qualifications to play a role in this workforce has long been questioned, prompting widespread calls for education across the spectrum of medical training. Adult learning theory indicates that for education to be effective, a perceived need to learn must first be established. Medical specialists have to perceive genomic medicine as relevant to their clinical practice. Here we review what is currently known about medical specialists’ perceptions of genomics, compare these findings to those from the genetics era, and identify areas for future research. Previous studies reveal medical specialists’ views on the clinical utility of genomic medicine are mixed, and are often tempered by several concerns. Specialists generally perceive their confidence and understanding to be lacking; subsequently they welcome additional educational support, although specific needs are rarely detailed. Similar findings from the genetics era suggest these challenges are not necessarily new, but on a different scale and relevant to more specialties as genomic applications expand. While existing strategies developed for genetic education and training may be suitable for genomic education and training, investigating the educational needs of a wider range of specialties is critically necessary to determine if tailored approaches are needed, and, if so, to facilitate these. Other interventions are also required to address some of the additional challenges identified in this review, and we encourage readers to see education as part of a broader implementation strategy.